Testing efficacy of a multi-site environmental education programme in a demographically and biologically diverse setting. (12th December 2019) - Brown, Ella R.; Imron, Muhammad Ali; Campera, Marco; Nekaris, K.A.I.
Summary: Creating and assessing relatively broad conservation education curricula is important when trying to reach a variety of students. We used a curriculum centred around a storybook in 12 schools in four separate areas of Indonesia, reaching 529 students. We visited each school twice, and taught the ecology and importance of the target taxa, Indonesia's seven threatened slow loris species ( Nycticebus spp.). Through cultural consensus analyses and structural equation modelling, we found that students from all regions showed improvements in knowledge, and that the distance from the forest to where children lived, teachers' use of given education materials, and students' use of the storybook all affected student performance in drawing and essay accuracy. Here we make suggestions for creating and evaluating multi-site environmental education programmes. We recommend creating curricula that are not inclusive of any particular community; providing teachers with materials to supplement a conservation intervention; giving each child their own copy of any visual materials used in the lessons; following up with students and teachers about the use of such materials; and interviewing teachers and students regarding their experience with and attitudes towards the study subject. Furthermore we suggest practitioners share their materials and have confidence in adapting them for other species and locations.